Young, Female and Black - Mirza, Heidi Safia (Taylor & Francis, 1992)
Young black women bear all the hallmarks of a fundamentally unequal society. They do well at school, contribute to society, are good efficient workers yet, as a group they consistently fail to secure the economic status and occupational prestige they deserve. This book presents a serious challenge to the widely held myth that young black women consistently underachieve both at school and in the labour market. In a comparative study of research and writig from America, Britain and the Caribbean Young, Female and Black re-examines our present understanding of what is meant by educational underachievement, the black family and, in particular, black womanhood in Britain.